(untitled) - Weinschenk-Foerster, Dipl. Agr. Biol. M. (Thailand, 1996)
The documentation is based on the evaluation of available data and studies as well as interviews with representative of administrative authorities, other invilved local organizations. institutions as well as the private sector.
Keywords: Refuse and refuse disposal,Rác thải và những thứ bỏ đi; Chiang Mai (Thailand),Chiang Mai